Daya Terima dan Kandungan Gizi Kue Bolu Cukke Subtitusi Dedak Padi - Andi Bida Purnamasari; Putri Athira Azis (Jurusan Biologi Universitas Negeri Makassar, 2022)
This study aims to determine the acceptability and nutritional content of sponge cake with rice bran substitution. This research was carried out at the Biology Laboratory of STKIP Pembangunan Indonesia in 2019. This research began with rice bran sifting followed by making sponge cake, panelist assessment, analysis of nutritional content, data processing and analysis and finally the preparation of research reports. Protein content analysis using the Kjeldahl method. Analysis of fat content using the gravimetric method. Analysis of carbohydrate content using the titrimetric method. Receiving power data were analyzed using frequency distribution. The level of difference in acceptability was analyzed using the Kruskal-Wallis test. The results of this study indicate that the acceptability based on the taste aspect in the three groups is relatively the same (p = 0.275) but based on the Mean Ranks, the 25% sample group is preferred by the panelists. There are color differences in the four sample groups (p=0.000), the 25% sample group is preferred by the panelists. There were differences in aroma in the three sample groups (p=0.013), the 25% sample group was preferred by the panelists. The acceptability based on the taste aspect in the three sample groups was relatively the same (p=0.733) but based on the Mean Ranks, the 25% sample group was preferred by the panelists. The highest fat content is found in 25% rice bran substitution, the highest proteincontent is in 25% rice bran substitution, while the highest carbohydrate content is in 50% rice bran substitution.